Molecular mechanisms regulating the chromatin architecture and gene transcription in human diseases - Feng, Y (2022)

(untitled)
In this thesis, I leveraged multi-omics, computational and functional analysis to shed light on the 3D genome organization and its impact on transcriptional regulation in pancreatic ductal adenocarcinoma (PDAC) and dilated cardiomyopathy (DCM), which are two of the world's deadliest diseases.